DIAGNOSTIC ACCURACY OF ULTRASONOGRAPHY IN DIAGNOSING MAXILLARY SINUSITIS: Maxillary Sinusitis - Shakeel, Yasar; Khan, Muhammad Asad; Mehmood, Rashid (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the diagnostic accuracy of ultrasonography in diagnosing maxillary sinusitis while keeping magnetic resonance imaging as gold standard. Study Design: Cross sectional, validation study. Place and Duration of Study: Radiology Department Combined Military Hospital Rawalpindi, from Mar 2014 to Sep 2014. Material and Methods: Consenting three hundred and ninety-one patients diagnosed clinically as a case of maxillary sinusitis at Combined Military Hospital Rawalpindi during the study period fitting the inclusion criteria were selected. Ultrasonography of maxillary sinuses focusing on mucosal thickening, fluid level and cystr polyp was done for all patients. After ultrasonography all patients underwent MRI at our department to look for mucosal thickening, fluid levels and total opacity appearing hyperintense on T2 weighted sequence. Diagnostic accuracy of ultrasonography was evaluated in the diagnosis of maxillary sinusitis. Results: The sensitivity of Ultrasonography in diagnosis of maxillary sinusitis keeping MRI as Gold Standard was quite low at 40.15%. The ability (specificity) of Ultrasonography in diagnosis of maxillary sinusitis taking MRI as Gold Standard was good i.e. 84.67%. The diagnostic accuracy was encouraging at 55.75%. Conclusion: Ultrasonography had low sensitivity but high specificity in diagnosis of maxillary sinusitis.